FRI0241 The effect of abatacept on cytokine profile in patients with rheumatoid arthritis. (15th June 2017) - Borisova, MA; Lukina, GV; Sigidin, Y; Luchihina, EL; Karateev, DE; Novikov, A; Alexandrova, E; Aronova, E; Glukhova, S; Nasonov, E
Abstract : Background: Pathological activation of T-cells with the overproduction of pro-inflammatory cytokines is playing a major role in the pathogenesis of rheumathoid arthritis (RA). The influence of the selective co-stimulation modulator abatacept (ABA) on the dynamics of cytokine profile in patients with RA is not fully understood. Objectives: To assess the changes in cytokine profile in patients treated with ABA. Methods: 44 patients with RA and an inadequate response to synthetic DMARDs or biologics were enrolled in the study. Most of them were middle aged females (46, 9±13, 9 years) with median RA duration 2 years (1, 4–3), high disease activity (DAS28=5, 2±0, 8), RF-positive (80%) and ACPA-positive (79, 5%). 16 healthy individuals were included in the study as control. The serum levels of IL-1, IL-6, IL-17, TNF-α, VEGF, IP-10 (pg/ml) were measured by ELISA immunoassay, YKL-40 by MicroVue immunoassay at baseline and 24 weeks. Disease activity was measured by DAS28, results were assessed every 12 weeks by EULAR criteria. ABA was administered intravenously every 4 weeks. Results: Levels of IL-6 (2.4 (1, 1–6, 4) vs 0.7 (0, 62–1, 0), p=0, 0002), YKL-40 (97 (68, 4–97, 9) vs. 64 (52, 4–107, 5), p=0, 03), IP-10 (21 (12, 9–49, 8) vs 14 (9, 2–15, 2), p=0, 005) were significantly higher in patients with RA compared to control. ABA significant reduced disease activity already after 12 weeks of therapy (p<0, 05). After 24 weeks of ABA therapy good and moderate response by EULAR criteria was achieved in 86%, low disease activity by DAS28 in 52%. By the 6-th month ABA significant decreased levels of IL-6 (1, 29 (0, 9–2, 2, p=0, 0006), IP-10 (14 (7, 5–28), p=0.007) as well as MMP3: before 30.1 (13–82), after 24 weeks 10 (7.4–55), p=0.0003 and RF: before 218 (9.6–187), after 24 weeks 159 (9.7–155), p=0.02. Lowering of the IL-6 (r=0, 5) and IP-10 (r=0, 32) levels were significantly (p<0.05) associated with a decrease of DAS28. Conclusions: ABA therapy leads to a significant reduction in serum levels of IL-6, IP-10, MMP3 and RF. The serum levels of IL-6 and IP-10 correlate with decrease activity of RA. Disclosure of Interest: None declared